Multifaceted Management of the Postthrombotic Syndrome - Nayak, Lina; Vedantham, Suresh (Seminars in Interventional Radiology, 2012)
The postthrombotic syndrome (PTS) is a frequent cause of chronic pain, swelling, ulceration, and disability in patients with lower extremity deep vein thrombosis (DVT). As interventional radiologists are consulted on more patients with chronic DVT and PTS, their management strategies must be informed by a balanced understanding of the different facets of chronic DVT care and the available treatment options. This article provides an overview of the important elements of a multifaceted approach to the management of patients with PTS that includes pharmacological, physiological, and endovascular aspects of care.
Keywords: postthrombotic syndrome; iliac vein; stent; endovenous thermal ablation; deep vein thrombosis